Antropologia Educacional Histórico-Cultural Alemã: bases teórica e epistemológica - Vieira, Karina Augusta Limonta [UNESP] (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2018)
This paper presents and debates the theoretical and epistemological benchmarks of the current German Historical-Cultural Anthropology of Education (or AEHCA - from the Portuguese Antropologia Educacional Histórico-Cultural Alemã), guided by two leading questions, namely: (1) what is your field of knowledge and (2) what are your theoretical and epistemological benchmarks? The AEHCA regards education as science and takes the human being and their educational dimensions as a starting point, which turns the education into a constructive and reflexive field of knowledge through a transdisciplinary, interdisciplinary, transcultural and intercultural approach, open to theories and methods. Ultimately, this is what leads to a reflection on the human being in itself and their education.

Este artigo apresenta e discute as bases teórica e epistemológica da atual Antropologia Educacional Histórico-Cultural Alemã (AEHCA), tendo duas questões norteadoras: (1) qual é o seu campo de conhecimento e (2) quais são suas bases epistemológicas e teóricas? A AEHCA reconhece a educação como ciência e tem como ponto de partida o ser humano e suas dimensões educacionais, fazendo da educação um campo de conhecimento construtivo e reflexivo por meio de uma abordagem interdisciplinar, transdisciplinar, intercultural e transcultural, aberta a teorias e métodos, o que leva à reflexão sobre o ser humano em si e sua educação.
German Historical-Cultural Anthropology of Education: theoretical and epistemological benchmarks
Keywords: anthropology of education; epistemology of education; fundamentals of education; antropologia educacional; epistemologia da educação; fundamentos da educação